2016
DOI: 10.1042/bsr20160106
|View full text |Cite
|
Sign up to set email alerts
|

TRPV6 modulates proliferation of human pancreatic neuroendocrine BON-1 tumour cells

Abstract: Highly Ca2+ permeable receptor potential channel vanilloid type 6 (TRPV6) modulates a variety of biological functions including calcium-dependent cell growth and apoptosis. So far, the role of TRPV6 in controlling growth of pancreatic neuroendocrine tumour (NET) cells is unknown. In the present study, we characterize the expression of TRPV6 in pancreatic BON-1 and QGP-1 NET cells. Furthermore, we evaluate the impact of TRPV6 on intracellular calcium, the activity of nuclear factor of activated T-cells (NFAT) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…The presence of TRPV6 in neuroendocrine cancer cells mediates cell proliferation: TRPV6 downregulation reduces cell growth by approximately 30 % and leads to declined CCND1 and CDK4 expression, without affecting CCND2. TRPV6mediated cell proliferation is dependent upon NFAT-Ca 2+ activation as shown by TRPV6 downregulation [47]. These data are in accordance with previously reported role for TRPV6 in both prostate and breast cancer proliferation and growth.…”
Section: Trp Channels Netsupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of TRPV6 in neuroendocrine cancer cells mediates cell proliferation: TRPV6 downregulation reduces cell growth by approximately 30 % and leads to declined CCND1 and CDK4 expression, without affecting CCND2. TRPV6mediated cell proliferation is dependent upon NFAT-Ca 2+ activation as shown by TRPV6 downregulation [47]. These data are in accordance with previously reported role for TRPV6 in both prostate and breast cancer proliferation and growth.…”
Section: Trp Channels Netsupporting
confidence: 92%
“…Several TRP channels result de-regulated in cancer cells and have been suggested as valuable markers in predicting cancer progression and as potential targets for pharmaceutical therapy [7,44] . Concerning NET, TRP channels have been involved in neurosecretion and cell proliferation and in particular TRPM8, TRPV1 and TRPV6 in pancreatic NET BON cells lines as well as in primary PNET cells [45][46][47].…”
Section: Trp Channels Netmentioning
confidence: 99%
“…Since these pathways were involved in β-cell proliferation (62,63), these data strongly suggested that TRPV6 may trigger INS-E cell growth via calcineurin/NFAT-and ERK1/2-dependent mechanisms. Notably, similar data indicating the link between TRPV6/NFAT signalling and cell proliferation were described in human neuroendocrine pancreatic BON cells (64). By contrast, to promitogenic effects of TRPV2 and TRPV6 in insulin producing cells, it was demonstrated that TRPV4 activation by hIAPP stimulate β-cell death.…”
Section: Trpvs In Controlling β-Cell Growth and Deathsupporting
confidence: 50%
“…Knockdown or overexpression of TRPV6 in cultured cancer cells showed mixed effects in increasing/decreasing proliferation and/or apoptosis (Chow, Norng, Zhang, & Chai, 2007;V Lehen'Kyi, Flourakis, Skryma, & Prevarskaya, 2007;V. Lehen'kyi et al, 2012;Raphael et al, 2014;Skrzypski et al, 2016). Future studies are needed to clarify the role of TRPV6-[Ca 2+ ]i-PP2A in prostate and colon cancer initiation and progression and its relationship to IGF1 receptor-PI3 kinase-AKT-mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%